Reducing Energy Demand in Concrete Pavements by the Use of Blended Cements - Réka Szpotowicz; Csaba Tóth (Acta Technica Jaurinensis)
This research explores strategies to minimise energy consumption and enhance environmental sustainability in road construction. Focusing on concrete pavement structures, the study evaluates the impact of substituting Portland cement with environmentally friendly alternatives such as fly ash and blast furnace slag. A comprehensive model is employed to analyse the energy demands of different pavement types, considering various cement replacements over their lifetime, from the initial extraction of materials to the conclusion of construction. Results indicate an energy saving potential of 8.63% by substituting 10% of Portland cement with fly ash, while an impressive reduction of 58.63% in cement production energy is achieved by replacing Portland cement with 80% blast furnace slag. The study underscores the significant role of cement variations in mitigating energy consumption, emphasizes the potential of blast furnace slag as a sustainable alternative as well as highlights the significance of alternative cement types in reducing energy consumption in concrete pavement construction, aligning with environmental sustainability goals and offering insights for more eco-friendly infrastructure development.